Efeito gastroprotetor da Riparina III em camundongos submetidos ao modelo agudo de lesão gástrica induzida por etanol e possíveis mecanismos envolvidos - Vale, Larice de Carvalho (2020)
Gastric ulcer or peptic ulcer is a chronic inflammatory disease of the stomach and duodenum, which presents lesions in the lined part of the stomach, with characteristics of inflammation, irritation and cell loss, which can progress to gastric cancer. For the treatment of this disease, there are some medications, which, although showing good results, cause some adverse effects, such as headache, dizziness and gastrointestinal disorders. In this context, the search for new therapeutic alternatives is of paramount importance and there has been great interest in the search for natural products. Therefore, the focus of the work is the study of Riparina III (Rip III), a substance initially isolated from the green fruit of Aniba riparia, with promising potential, since important properties such as anti-inflammatory and antinociceptive have already been reported. Based on these considerations, the objective was to evaluate the effect of Rip III in the acute model of gastric lesion induced by ethanol in mice and possible mechanisms involved. For that, male Swiss mice, weighing between 25-30g, were divided into different groups with 6 animals each. To assess ulcer induction by ethanol and the potential gastroprotective effect of Rip III (50mg / kg), a dose of 0.2 mL / animal of ethanol administered orally by gavage after pretreatment with the drugs was used. Subsequently, both macroscopic (percentage of ulcerated area) and microscopic evaluations were performed using histopathological parameters (loss of epithelial cells, edema, hemorrhage, inflammatory infiltrate, and number of mast cells). To investigate the mechanisms involved, evaluations were made on the participation of potassium channels sensitive to ATP (K + ATP), prostaglandins (PGs), vanilloid receptors (TRPV1) and nitric oxide (NO). Additionally, nitrite levels were also measured to confirm the participation of NO, in addition to the expression of induced nitric oxide synthase (iNOS) through the immunohistochemistry technique. The involvement of oxidative stress, such as reduced glutathione (GSH) and malondialdehyde (MDA) were also evaluated. The results showed that Rip III previously administered to ethanol exhibited a potent gastroprotective effect, demonstrated by microscopic analysis by reducing the loss of epithelial cells, edema, inflammatory infiltrate and number of mast cells. It was observed that pretreatments with L-NAME (iNOS inhibitor) and glibenclamide (potassium channel blocker) reversed the gastroprotective effect of Riparina III, indicating that this substance possibly acts in such pathways. Rip III restored nitrite levels and its gastroprotective effect does not show involvement of prostaglandins or TRPV-1 receptors. It was also found that Rip III significantly increased GSH levels and reduced lipid peroxidation in this model. In conclusion, the results obtained indicate that Riparina III has gastroprotective activity against gastric lesions induced by ethanol, and this action seems to involve the participation of nitric oxide, potassium channels sensitive to ATP, in addition to its potential antioxidant effect.